O cotidiano da infância e das práticas educativas da educação do campo : categorias em construção na história da educação - Araújo, Elis Regina Nunes Mota (2016)
This work deals with the theme of childhood and educational practices in peasant school of field education. It tries to understand the daily life of childhood in a rural community with economic, social and cultural practices of field life, from the perspective of adults and children who live there and constitute a community. The empirical research has been developed in the Fortaleza Settlement, located in the village Aningas, municipality of Nossa Senhora da Glória, Sergipe. The issues addressed in this research focuse on the daily life of peasant childhood in community and educational practices of the settlement school, from the perspective of Social History of Childhood studies and methodological orientation of observation and analysis of which transits between the totality, the specificity and uniqueness of this object of study. The data were collected through semi-structured interviews, records in the diary of field and of the drawings of children in the period from June 2014 and March 2015. The results show that the struggle for land means the fight for school education and that the daily life of childhood has job, interlocked with playing (wheel, tag, hide and seek), as a relevant element in the formation of the subjects, what evidences there is specificity in field childhood, historically demarcated by contradictions.